Geschichte der altgermanistischen Edition - Schubert, Martin; Lange, Judith (Bausteine zur Geschichte der Edition, 2023)
This volume portrays the practice of Old German textual criticism from its beginnings in the 19th century to the early 20th century, examining the most important editions and personalities from the discipline's history and presenting its methodological development alongside detailed analyses of methods and problem-solving strategies. The volume closes with an outlook on the various research controversies and the impact of editorial approaches.